SCID (Severe Combine Imunofeficiency): Tinjauan Literatur - Suherman, Juwita Ninda; Farizi, Taufiq Al (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Severe Combined Immunodeficiency (SCID) is a group of rare genetic disorders that affect the development and function of the immune system. This literature review aims to summarize the current understanding of SCID, including pathophysiology, clinical manifestations, diagnostic approaches, and therapeutic strategies. A PubMed database search was performed using the search terms “Severe Combined Immunodeficiency” and “SCID”. Relevant articles, including original research, case reports, and reviews, were selected for inclusion. SCID is characterized by severe deficiencies in the number and function of T cells, B cells, and sometimes Natural Killer (NK) cells. This disorder is caused by mutations in one or more genes involved in the maturation of immune cells, which are inherited in an autosomal recessive or X-linked pattern. As a result, affected infants are highly susceptible to life-threatening opportunistic infections. Clinical symptoms of SCID usually appear within the first few months of life, with recurrent infections as the main manifestation. Diagnostic approaches include newborn screening, complete blood count, measurement of immunoglobulin levels, and T cell function tests. Hematopoietic stem cell transplantation (HSCT) remains the therapy of choice, with gene therapy a promising approach. Although SCID treatment has made significant progress, challenges remain in terms of early diagnosis, availability of suitable donors, and post-transplant complications. Further research is needed to optimize therapeutic strategies and improve long-term outcomes for SCID patients.